ANALISIS YURIDIS UJARAN KEBENCIAN YANG DILAKUKAN OLEH JERINX KEPADA IKATAN DOKTER INDONESIA DITINJAU DARI PERSPEKTIF RESTORATIVE JUSTICE - Ginanjar Rizki Danang Prasetyo (At-Tanwir Law Review, 2021)
This writing aims to find out how the development of technology and digital information has doubled the acceleration of messages through electronics, thus giving rise to practices and values in various content in digital media. In this era of progress, it is undeniable that all forms of technology are increasingly developing rapidly every day, one of which is social media, social media brings users to facilitate all forms of activities in daily life and even makes users feel dependent on social media. It is undeniable that with the development of technology and information there are various problems, which are known as Cyber Crime. Cybercrime is an act where someone misuses digital technology or commits a crime not directly but through the intermediary of electronic devices such as cellphones, tablets, computers, etc. and is used on internet technology digitally and with the intention of violating the law. One of the forms of crime is hate speech, which is a crime nowadays that many people violate language politeness. Hate speech is an action taken by one or more people in the form of incitement, provocation, or insult to others in several aspects such as ethnicity, religion, race, gender, skin color, disability, sexual orientation.